An Academic and Cultural Transition Course for International Students: Efficacy and SocioEmotional Outcomes - Brunsting, Nelson C.; Smith, Andrew C.; Zachry, Corinne E. (Journal of International Students, 2018)
The current study details changes in first-year international undergraduate students’ perceived knowledge of, confidence in, and usefulness of intercultural skills in specific US university contexts after completing a semester-long academic and cultural transition course at a mid-sized private university. Results revealed significant increases in participants’ (n= 42) perceived intercultural competence, perspective shifting, suspending judgment, self-advocacy, and interacting in class with students of other cultures; participants also reported significantly higher campus belonging and social support than a comparison group of students at the university who were not enrolled in the course (n = 32). These findings provide initial evidence for the potential of transition courses to increase intercultural skills and campus belonging for first-year undergraduate international students attending US universities.